1994
DOI: 10.1128/jcm.32.1.98-104.1994
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bovine trichomoniasis with a specific DNA probe and PCR amplification system

Abstract: Trichomoniasis is a widespread, economically important venereal disease of cattle which causes infertility and abortion. Effective control of trichomoniasis has been impeded by the insensitivity of traditional diagnostic procedures, which require the isolation and cultivation of the parasite, 7Titrichomonasfoetus, from infected cattle. We developed a 0.85-kb T.foetus DNA probe by identifying conserved sequences in DNAs from T.foetus that were isolated from cattle in California, Idaho, Nevada, and Costa Rica. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…DNA was purified from the 16 Saskatchewan isolates and the American Type Culture Collection Austrian isolate, 50151. These DNAs were subjected to the T. foetus-specific single-band PCR test of Ho et al (9). The expected 162-bp PCR product was strongly amplified from 16 isolate DNAs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA was purified from the 16 Saskatchewan isolates and the American Type Culture Collection Austrian isolate, 50151. These DNAs were subjected to the T. foetus-specific single-band PCR test of Ho et al (9). The expected 162-bp PCR product was strongly amplified from 16 isolate DNAs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Oligonucleotide primers were synthesized with a Cyclone DNA synthesizer (Millipore, Bedford, Mass.). The TF1-TF2 single-band PCR test used published primer sequences (9). TCO-1 amplifications used the 57-mer, GGATCCATCGGAATTAAAAAACCGAAAAA AAAATTTAGGGTAAAAAAAATCATTACA, complementary to the control region of a trichomonad cell division control-like sequence (20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large variety of molecular protocols were developed for the detection of T. foetus in cattle and felines (HO et al, 1994;FELLEISEN et al, 1998;GOOKIN et al, 2002;BONDURANT et al, 2003;GRAHN et al, 2005). Many tests rely on amplification of the 5.8S rRNA gene sequences using ITS1 and ITS2, which are more conserved regions among isolates (FELLEISEN, 1997).…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…The sensitivity of this assay has been controversial since a subsequent study reported that of 26 culture-positive bulls only 10 or 14 animals were identified as being infected by the DNA probe assay (1). More recently, using PCR amplification of repetitive genomic sequences of DNA, Ho and coworkers (11) were able to identify 90% of infected samples from naturally infected bulls, while uninfected bulls were all classified as negative with the same PCR probe. This is promising.…”
mentioning
confidence: 99%